Implementing Alternative Assessment Strategies in Chemistry Amidst COVID-19: Tensions and Reflections - Poh Nguk Lau; Yek Tann Chua; Yiwei Teow; Xuejia Xue (MDPI AG, 2020)
The COVID-19 pandemic in the first quarter of 2020 resulted in the worldwide disruption of teaching and learning in main stream schools and in institutes of higher learning. Singapore was not spared. With the closure of schools in early April, it was imminent that the delivery and assessment of our freshman general chemistry course must be overhauled for the new semester. While the delivery of Home-based Learning (HBL) was a challenge for all educators, it was a mammoth roadblock for chemistry courses because of laboratory classes. Besides being thrusted to learn and use new technology tools for online lessons, instructors also had to quickly explore and design alternative assessments to substitute in-person written examinations and tests. This paper documents the struggles that played out in the decision to implement concept map assessments and "split-half" laboratory classes for safe distancing. Although these interventions are not novel, we confronted tensions as we sought to address academic integrity, administrative guidelines, and our own inadequacy particularly in concept map assessments. In light of positive and negative feedback from both staff and students, lessons were drawn to enhance future implementation and for further research.